2021
DOI: 10.1002/ghg.2123
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and development of the multicycle of CO2 mineralization with wastewater under standard conditions

Abstract: CO2 mineralization is promising for carbon capture and storage (CCS). The multiple reuses of monoethanolamine (MEA) as absorbents for CO2 absorption and carbonate generation with minerals in wastewater between 20 and 25°C at atmospheric pressure (standard conditions) efficiently reduce both cost and energy penalties for industrial application. In this study, the multicycle of CO2 mineralization was performed in three steps: absorption, precipitation, and regeneration. We found that 5 wt.% MEA solution has grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…The calculation error of CO 2 absorption capacity ranged from 2.74 to 16.20%. Furthermore, these results were similar to those reported in the literature [17,24,[46][47][48]. However, the amount of CO 2 absorbed varied because of independent factors, such as human error or external factors.…”
Section: Effects Of the Developed Model Of Co 2 Absorption Capacitysupporting
confidence: 90%
See 4 more Smart Citations
“…The calculation error of CO 2 absorption capacity ranged from 2.74 to 16.20%. Furthermore, these results were similar to those reported in the literature [17,24,[46][47][48]. However, the amount of CO 2 absorbed varied because of independent factors, such as human error or external factors.…”
Section: Effects Of the Developed Model Of Co 2 Absorption Capacitysupporting
confidence: 90%
“…The previous study [24] showed a single step of precipitation under standard conditions, whereas we performed precipitation twice (100 and 50 mL), and the results were compared, as shown in Figure 3.…”
Section: Effects Of the Increased Number Of Precipitation Stepsmentioning
confidence: 99%
See 3 more Smart Citations